Humanistyka w świecie edukacji technicznej - Sommer, Hanna (Wydawnictwo Politechniki Łódzkiej, 2017)
This article draws attention to the role of the humanities in the context of the development of the world of technologies and engineering efficiency. Both of these areas play a very important role in the functioning of societies. The modern labour market is looking for well educated professionals who can work in even the most distant fields of knowledge. At present, it is not enough to have a narrow profile education. Humanities and social sciences should play an important role in technical education as it is people who are the creators of technological progress. People of the 21st century should be sensitive and able to use his knowledge wisely. A well-educated "humanist engineer" in his work should be the guarantor of the primacy of humans over the technique (technology?).
Humanities in the world of technical education
Keywords: stechnicyzowany świat; inżynier humanista; nowe wymagania pracodawców względem pracowników; elastyczny pracownik; humanistyczny aspekt nauk ścisłych; technological world; humanities engineer; new requirements of employers towards employees; flexible employee; humanistic aspect of science